2018
DOI: 10.1002/jcp.26632
|View full text |Cite
|
Sign up to set email alerts
|

Neural differentiation of human adipose‐derived mesenchymal stem cells induced by glial cell conditioned media

Abstract: Adipose-derived mesenchymal stem cells (ASCs) may transdifferentiate into cells belonging to mesodermal, endodermal, and ectodermal lineages. The aim of this study was to verify whether a neural differentiation of ASCs could be induced by a conditioned medium (CM) obtained from cultures of olfactory ensheathing cells (OECs) or Schwann cells (SCs). ASCs were isolated from the stromal vascular fraction of adipose tissue and expanded for 2-3 passages. They were then cultured in OEC-CM or SC-CM for 24 hr or 7 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 35 publications
8
25
0
Order By: Relevance
“…In accordance with previous studies ( Calabrese et al, 2015 ), cells were immunopositive for typical MSC markers (CD 44, CD 73, CD 90, and CD 105) and immunonegative for typical hematopoietic stem cell markers (CD 14, CD 34, and CD 45). Moreover, as reported recently ( Lo Furno et al, 2018 ), an ASC neural-like phenotype by using OEC-CM or SC-CM was here confirmed by the increased immunopositivity for Nestin, PGP9.5, and GFAP (Figure 1 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In accordance with previous studies ( Calabrese et al, 2015 ), cells were immunopositive for typical MSC markers (CD 44, CD 73, CD 90, and CD 105) and immunonegative for typical hematopoietic stem cell markers (CD 14, CD 34, and CD 45). Moreover, as reported recently ( Lo Furno et al, 2018 ), an ASC neural-like phenotype by using OEC-CM or SC-CM was here confirmed by the increased immunopositivity for Nestin, PGP9.5, and GFAP (Figure 1 ).…”
Section: Resultssupporting
confidence: 89%
“…In our previous studies ( Lo Furno et al, 2013b , 2018 ), a successful differentiation of ASCs toward neural-like elements was achieved by using a conditioned medium (CM) from cultures of Schwann cells (SCs) or olfactory ensheathing cells (OECs). This differentiation was documented by the increased expression of typical neural markers (Nestin, PGP9.5, MAP2, Synapsin I, GFAP).…”
Section: Introductionmentioning
confidence: 99%
“…Neurospheres generated from the canine ASCs were used to enrich for neural lineages expanded enough to transplant (19) and when grown in hypoxia showed higher expression of neuronal marker nestin (20). Recently, neural differentiation of human ASCs was evoked by conditioned medium obtained from glial cells (21).…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) as desirable cell carriers can be easily obtained, expanded, and genetically engineered to express and secret therapeutic proteins in-vivo (21)(22)(23)(24). Human Wharton's jelly mesenchymal stem cells (hWJMSCs) are multipotent stem cells which showed the potential to differentiate into mesodermal, ectodermal and endodermal lineages (25,26). Compared to adult and fetal stem cells, hWJMSCs show a higher proliferation rate and minimum stimulation of immune and in ammatory systems (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%